Academic Senate Minutes 2008-10-30 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 10/2 and 10/16 approved. Provost Report. Resolution Condemning Hate Crimes. Proposal for New Minor in Jewish Studies – First Reading. Chair-Elect Report. Statewide Senators Report. Special Report: The Athletics Program. Emergency Instructional Funding Resolution (resolution from the floor). CFA President Report. Good of the Order.